LRO biogenesis and function: what can we learn from mast cells? - Montero-Hernández, Juan Eduardo; Zhang, Kerui; Blank, Ulrich; Ménasché, Gaël (Frontiers in Cell and Developmental Biology, 2025)
Lysosome-related organelles (LROs) are specialized compartments with cell type-specific roles. In mast cells (MCs), which are tissue-localized hematopoietic effector cells, LROs refer to secretory lysosomes also known as secretory granules (SGs) containing numerous pre-formed inflammatory mediators including proteases, proteoglycans, lysosomal enzymes, histamine and serotonin. Their release during MC activation is responsible for allergic, inflammatory manifestations, the fight against parasitic agents or the neutralization of toxins. Here, we provide an overview of knowledge describing the mechanisms underlying the biogenesis, secretion and biological functions of LROs in MCs. Decoding molecular mechanisms involved in LRO biogenesis and biology of MCs will benefit i) to other immune or non-immune cell types containing LROs and ii) can be exploited to design novel therapeutic approaches for the treatment of allergic and chronic inflammatory diseases caused by MC activation.